Structural Analysis of the Luowei Orefield in Xidamingshan, Guangxi, China. Issue 1 (22nd October 2019) - Li, Saisai; Feng, Zuohai; Fu, Wei; Li, Zemin; Hu, Rongguo
Abstract: Many types of hydrothermal deposits (e.g. W, Bi, Pb, Zn, Ag) are confined by faults and hidden granodiorite in the Luowei Orefield in Xidamingshan, Guangxi, China. The orebodies in the Luowei W–Bi deposit are predominantly layered and distributed along bedding in sandstones of the Cambrian Xiaoneichong Formation. The orebodies in the Lujing Pb–Zn deposit are controlled mainly by west‐south‐west (WSW)‐trending faults, and those in the Fenghuangshan Ag deposit are controlled mainly by west‐north‐west (WNW)‐trending faults, which were reverse faults during mineralization and were later reactivated as sinistral strike‐slip faults. The Luowei fault was formed postmineralization and resulted in sinistral displacement of the subsurface granodiorite and the Cambrian strata. A tectonomagmatic mineralization model of the Luowei Orefield is proposed, and the following conclusions were made. (i) Under a regional N–S compressive stress regime, WSW‐ and WNW‐trending reverse faults and N–S‐trending tensional fractures were formed. (ii) Magma intruded along the tensional fractures. Under the force of magmatic thermodynamics, mineralizing fluid migrated along bedding planes in sandstones and formed W–Bi orebodies at favorable sites. Some fluid migrated along WSW‐ and WNW‐trending faults to sites farther from the magma source, forming vein‐type Pb–Zn and Ag orebodies. (iii) After mineralization, under E–W compression, a NW‐trending left‐lateral slip fault was formed, cutting the subsurface granodiorite and orebodies. Concurrently, sinistral shear slip occurred on WNW‐trending ore‐controlling faults. However, the small displacement on these faults did not change the overall distributions of the rock mass and orebodies. Abstract : The Luowei W–Bi deposit is dominated by bedding in Cambrian sandstone, and the Pb–Zn and Ag deposits are dominated by ∼E–W‐trending fault zones.Three deposits are located around the hidden granodiorite. WNW‐trending ore‐controlling faults were reverse faults during mineralization, and NW and WNW‐trending faults occurred sinistral shear slip after mineralization.